Women in jazz : musicality, femininity, marginalization - Buscatto, Marie (New York : Routledge, 2022)
"Women in Jazz: Musicality, Femininity, Marginalization examines the invisible discrimination against female musicians in the French jazz world and the ways women thrive as professionals despite such conditions. The author shines a light on the paradox for women in jazz: to express oneself in a "feminine" way is to be denigrated for it, yet to behave in a "masculine" manner is to be devalued for a lack of femininity. This masculine world ensures it is more difficult for women to be recognized as jazz musicians than it is for men-even when musicians, critics, and audiences are ideologically opposed to discrimination. Female singers are confined by the feminine stereotypes of their profession, while female instrumentalists must comport themselves into traditionally masculine roles. The author explores the academic and professional socializations of these musicians, the musical choice they make, and how they are perceived by jazz professionals as a result. First published in French by CNRS Editions in 2007 (and later reissued in paperback in 2018, with the author's postscript that "nothing much has changed"), Women in Jazz: Musicality, Femininity, Marginalization expands the conversation beyond the French border, identifying female jazz musicians as a discriminated minority all around the world"--
Keywords: Women jazz musicians -- France; Women jazz singers -- France; Jazz -- Social aspects -- France; Sex role in music; MUSIC / Genres & Styles / Jazz; SOCIAL SCIENCE / Women's Studies; MUSIC / Instruction & Study / Composition